Receptors for pro‐resolving mediators are increased in Alzheimer's disease brain. (21st January 2020) - Emre, Ceren; Hjorth, Erik; Bharani, Krishna; Carroll, Steven; Granholm, Ann‐Charlotte; Schultzberg, Marianne
Abstract: Neuroinflammation is a key element of AD pathology and conceivably a result of a disturbed resolution. Resolution of inflammation is an active process which is strictly orchestrated following the acute inflammatory response after removal of the inflammatory stimuli. Acute inflammation is actively terminated by specialized pro‐resolving mediators (SPMs) thereby promoting healing and return to homeostasis. Failed resolution may contribute to persistent neuroinflammation and aggravate AD pathology. BLT1 (leukotriene B4 receptor) and ChemR23 (chemerin receptor 23) are receptors for the SPM resolvin (Rv) E1 and are important clinical targets for ending inflammation. In AD, the levels of SPMs are decreased, and pro‐inflammatory mediators are increased. In the current study, the distribution of BLT1 and ChemR23 receptors in control brains and in AD as well as correlations with AD pathology was examined for the first time. BLT1 and ChemR23 were analyzed in different regions of post‐mortem human brain from cases with AD, early‐onset AD and mild cognitive impairment (MCI) and healthy controls, using western blotting and immunohistochemistry. BLT1 and ChemR23 were detected in neurons and glial cells in all examined regions of the human brain, with markedly higher levels in AD than in controls. The receptor levels correlated with the density of staining for the inflammation markers HLA‐DR and YKL‐40 for microglia and astrocytes, respectively, and elevated staining coincided with high Braak stages in AD. The relative staining densities of these receptors were higher in the basal forebrain, cingulate gyrus and hippocampal regions compared to the cerebellum and frontal cortex (BA46). In conclusion, alterations in the expression of the resolution receptor BLT1 in AD have not been reported previously and the changes in both BLT1 and ChemR23 suggest a disturbed resolution pathway in several regions of the AD brain that may play a role in disease pathology.